Protective activity of specific transfer factor against Salmonella typhimurium infection - Yousif, A. A.; Khalifa, K. A.; Al-Samarrae, S. A.G. (The Iraqi Journal of Veterinary Medicine, 2021)
Specific transfer factor (TF) extracted from spleens of sensitized and non-sensitized guinea pigs to study the efficacy of transfer of cellular immunity specific for salmonella . Two groups each of five guinea pigs were used for in vivo TF preparation. The First group was inoculated with 1 ml of aromatic dependent Salmonella typhimurium SL 1479 vaccine at a dose of 10' cfu/ml intramuscularly twice at two weeks intervals. The second group was injected with trypticase soy broth similarly . These two groups used as a donor for TF, and TFn respectively. Twenty one recipient guinea pigs were divided into three groups, the first group was TF at a dose of 1 ml equivalent to 5X10 cell intramuscularly three times/2 days intervals, Similarly the second group was given TF, where as the third group was given PBS- Cell mediated immunity in recipient animal was evaluated by delayed type hypersensitivity - skin test, Macrophage migration inhibition test (MIF) and then challenged with virulent Salmonella typhimurium. The TFt recipient group induced skin test and showed migration indices less than 0.8 and overcome the challenge organism. Contrary to TFn & PBS recipient groups which did not show any response for skin test and given migration indices more than 0.8 and did not show resistance for virulent Salmonella typhimurium .